Draft Genome Sequence of an Extensively Drug-Resistant Mycobacterium tuberculosis Manu-Ancestor Spoligo-International Type 523 Isolate from Thailand - Regmi, Sanjib M. (Genome Announc, 2015)
We present the draft genome sequence of DS-16780, with a rare spoligo-international type (SIT) 523 (777777777777771) genotype, which reveals an extensively drug-resistant Mycobacterium tuberculosis (XDR-TB) phenotype. The isolate is a representative of clonal XDR-TB from the western part of Thailand.